Pengembangan Modul Keanekaragaman Hayati Berbasis Pangan Tradisional Nusa Tenggara Timur - Tpoenifu, Evi Yulinda; Mamangkey, Jendri; Silalahi, Marina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This study aimed to develop a module for biology based on the local wisdom of East Nusa Tenggara (NTT) traditional cuisine for high school students, particularly for the 10th grade, focusing on the topic of biodiversity. This also focused on assessing the feasibility of the module and evaluating students' responses to its development.The development model used in this study was research and development (R&D), involving several stages of potentials and problems, data collection, product design, design validation, and design revision followed by collecting students’ responses to the module.The validation results from content experts, media experts, and language experts indicated that the local wisdom-based biology module was deemed valid. The average scores obtained from each expert's validation are as follows, content validation with a score of 0.81 in the